Digital transformation: exploring the significance of business digitalization for organizational success (2024)
This study explores the relationship between digital strategy, interorganizational collaboration, and innovation outcomes in Colombia, a country actively pursuing digital transformation. Utilizing structural equation modeling (SEM), the research reveals how these factors influence organizational success. Key findings indicate that a strong digital strategy enhances interorganizational collaboration, fostering partnerships and shared value. Supportive policies like the National Digital Strategy 2023-2026 have bolstered these efforts. However, the direct impact of digital strategy on innovation outcomes is limited, primarily due to challenges such as the digital divide and inadequate infrastructure in rural areas. Collaboration plays a crucial role in driving innovation, enabling organizations to share knowledge and resources for improved adaptability and problem-solving. Despite progress in internet access and digital adoption among small and medium enterprises (SMEs), gaps in infrastructure and skills remain. The study advocates for a multi-faceted approach involving policy support, private-sector initiatives, and academic research to address these barriers. Recommendations include enhancing digital infrastructure, promoting collaboration through innovation hubs, and aligning digital strategies with broader economic goals. These insights provide a roadmap for organizations navigating digital transformation in developing economies.